2022
DOI: 10.1177/1420326x221082198
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of airborne bacteria and fungi in different types of buildings in a temperate climate zone city, Kunming, China

Abstract: The characteristics of airborne bacteria and fungi in different types of buildings are still unclear. This article applied the culturing and next-generation sequencing methods to characterize the airborne bacteria and fungi in five types of buildings during winter in Kunming, China. Results showed that the mean concentrations of fungi in different buildings were similar (approx. 387 ± 388 CFU/m3). The highest culturable bacterial concentration was found in residences, while the lowest was in the library. Lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Both positive and negative correlations of bacterial concentration with temperature and RH were reported. [10][11][12][13][14] Some studies even observed noncorrelations. 15 The measurement method might be an important factor.…”
Section: Introductionmentioning
confidence: 99%
“…Both positive and negative correlations of bacterial concentration with temperature and RH were reported. [10][11][12][13][14] Some studies even observed noncorrelations. 15 The measurement method might be an important factor.…”
Section: Introductionmentioning
confidence: 99%